The Ulos Silalahi Woven Fabric Serves As a Significant Cultural Attribute Within The Silahisabungan District, Located In The Dairi Regency - Noviana Simbolon (Universitas Sumatera Utara, 2023)
The tittle of this research is Weaving Ulos Silalahi as a Cultural Attribute in Silahisabungan District, Dairi Regency. The objective of this study is to investigate the process involved in creating Ulos Silalahi Woven fabric and its utilization as a cultural symbol in traditional ceremonies within the Silahisabungan District. The present study employs ethnographic research methods. The findings indicated that the production of Ulos Silalahi Woven Fabrics commenced with the Mangunggas, which involves the bending of threads. Subsequently, the Manorha process is undertaken to string the threads into a humpalan. Finally, the Matibobok process is employed to create intricate designs on the fabric. The term